1990
DOI: 10.1002/j.1460-2075.1990.tb08136.x
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis B virus X-gene product trans-activates both RNA polymerase II and III promoters.

Abstract: The transcriptional regulatory activity of the human hepatitis B virus (HBV) X-gene product was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 50 publications
3
89
0
2
Order By: Relevance
“…Our studies represent the first example of a virusmediated event that induces RNA pol III gene activity through TFIIIB. Preliminary studies suggested that the HBV X protein enhances RNA pol III gene activity by targeting TFIIIC (2). In this study, results obtained from template commitment assays suggested that the DNA-binding activity of TFIIIC might be altered in Chang liver (CL) cells stably transformed with the X gene.…”
Section: Figmentioning
confidence: 78%
See 2 more Smart Citations
“…Our studies represent the first example of a virusmediated event that induces RNA pol III gene activity through TFIIIB. Preliminary studies suggested that the HBV X protein enhances RNA pol III gene activity by targeting TFIIIC (2). In this study, results obtained from template commitment assays suggested that the DNA-binding activity of TFIIIC might be altered in Chang liver (CL) cells stably transformed with the X gene.…”
Section: Figmentioning
confidence: 78%
“…These studies provide further evidence that X mediates an increase in TFIIIB activity which is responsible for the enhanced transcriptional capacity of the X-S2 cell extracts that was observed. Although these results demonstrate that X mediates a change in the TFIIIB component, previous studies suggested that X may target TFIIIC and alter its DNA-binding activity (2). Therefore, the relative activities of TFIIIC derived from the S-2 and X-S2 cell extracts were determined (Fig.…”
Section: Stably Transformed S-2 Cells Expressing Hbv X Exhibit Enhancmentioning
confidence: 85%
See 1 more Smart Citation
“…SV40 T antigen is a transactivator of polIII (72), which increases activity of TFIIIC by changing its abundance or phosphorylation state (73). TFIIIC has been shown to be the rate-limiting factor in the formation of polIII initiation complexes (71) and probably the target of trans-activators (74). The ability of X-protein to activate polIII is due to its interaction with TFIIIB rather than TFIIIC (69).…”
Section: Discussionmentioning
confidence: 99%
“…The HBx responsible cis-elements present in RNA polymerase II (RNAPII) promoters include AP-1, AP-2, ATF, c/EBP, NF-B sites, and serumresponsive element (3)(4)(5)(6)(7)(8)(9)(10)(11). One of the RNA polymerase III promoters is also transactivated by HBx (12). Several endogenous genes important for cell proliferation and acute inflammatory response, such as c-fos, c-jun, and human interleukin-8, are activated by HBx (3,7,13).…”
mentioning
confidence: 99%